What Cruising Infants Understand about Support for Locomotion. (30th November 2013) - Berger, Sarah E.; Chan, Gladys L. Y.; Adolph, Karen E.
<x xml:space="preserve">Abstract</x> "Cruising" infants can only walk using external support to augment their balance. We examined cruisers' understanding of support for upright locomotion under four conditions: cruising over a wooden handrail at chest height, a large gap in the handrail, a wobbly unstable handrail, and an ill‐positioned low handrail. Infants distinguished among the support properties of the handrails with differential attempts to cruise and handrail‐specific forms of haptic exploration and gait modifications. They consistently attempted the wood handrail, rarely attempted the gap, and occasionally attempted the low and wobbly handrails. On the wood and gap handrails, attempt rates matched the probability of cruising successfully, but on the low and wobbly handrails, attempt rates under‐ and overestimated the probability of success, respectively. Haptic exploration was most frequent and varied on the wobbly handrail, and gait modifications—including previously undocumented "knee cruising"—were most frequent and effective on the low handrail. Results are discussed in terms of developmental changes in the meaning of support.